The Good Soldier : A Tale of Passion - Ford, Ford Madox (England Penguin Books, 1972)
In 1998, the Modern Library ranked The Good Soldier 30th on its list of the 100 best English-language novels of the 20th century. Set just before World War I, the novel is told using a series of flashbacks in non-chronological order, through a rather unreliable narrator; for as it turns out, the story is not what we are led to believe at the beginning. The novel$1 (Bs original title was (3z(BThe Saddest Story(3y(B, from the novels opening lines (3z(BThis is the saddest story I have ever heard(3y(B; however, with the onset of World War I, the publishers asked Ford for a new title, to which he sarcastically suggested (3z(BThe Good Soldier(3y(B, and so it was named.s
Exploring the complex social and sexual relationships between two couples, one English, one American, this novel was regarded by its author as "the only novel of mine that I considered....at all to count". The novel has moments of comedy despite its catalogue of despair and tragedy.
Keywords: British -- Germany